The Reliability of Running Performance in a 5 km Time Trial on a Non-motorized Treadmill - Stevens, C. J.; Hacene, J.; Sculley, D. V.; Taylor, L.; Callister, R.; Dascombe, B. (International Journal of Sports Medicine, 2015)
The purpose of the study was to establish the reliability of performance and physiological responses during a self-paced 5 km running time trial on a non-motorized treadmill. 17 male runners (age: 32±13 years, height: 177±7 cm, body mass: 71±9 kg, sum of 7 skinfolds: 55±21 mm) performed familiarization then 2 separate maximal 5 km running time trials on a non-motorized treadmill. Physiological responses measured included heart rate, oxygen uptake, expired air volume, blood lactate concentration, tissue saturation index and integrated electromyography. Running time (1 522±163 s vs. 1 519±162 s for trials 1 and 2, respectively) demonstrated a low CV of 1.2% and high ICC of 0.99. All physiological variables had CVs of less than 4% and ICCs of >0.92, with the exception of blood lactate concentration (7.0±2 mmol·L−1 vs. 6.5±1.5 mmol·L−1 for trials 1 and 2, respectively; CV: 12%, ICC: 0.83) and the electromyography measures (CV: 8–27%, ICC: 0.71–0.91). The data demonstrate that performance time in a 5 km running time trial on a non-motorized treadmill is a highly reliable test. Most physiological responses measured across the 5 km run also demonstrated good reliability.
Keywords: reproducibility of results; physical endurance; sports performance; pacing strategy; electromyography; near-infrared spectroscopy